2009
DOI: 10.1159/000226290
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Prevalence among Pregnant Women and Birth Weight in Five Areas in China

Abstract: Objectives: To investigate the current prevalence of anemia among pregnant women in different areas of China and the association with birth weight and educational level. Methods: A total of 6,413 women aged 24–37 in the third trimester of pregnancy from five areas were randomly selected from all gravidas who gave birth in the hospitals from 1999 to 2003. Blood hemoglobin concentration (Hb) was measured by the cyanomethemoglobin method; Hb <110 g/l was considered as anemia. Results: The overall prevalence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
6
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
4
20
6
4
Order By: Relevance
“…The prevalence is considerably lower than that previously reported from India (84.9%),6 Nigeria (40.4%),11 Jimma town, southwest Ethiopia (41.9%),12 Peru (70.1%),17 and China (58.6%) 19. The present study findings of anemia were also lower than that stated in Ethiopian demographic and health survey reports of 2005, namely, 30.6% 8.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The prevalence is considerably lower than that previously reported from India (84.9%),6 Nigeria (40.4%),11 Jimma town, southwest Ethiopia (41.9%),12 Peru (70.1%),17 and China (58.6%) 19. The present study findings of anemia were also lower than that stated in Ethiopian demographic and health survey reports of 2005, namely, 30.6% 8.…”
Section: Discussioncontrasting
confidence: 75%
“…The present study showed no significant association between anemia and maternal age, housewives, monthly income, level of education; iron supplement but significant association was reported in previous studies); previous reports and the present study may be due to differences in monthly income and educational level 9,12,18,19,27…”
Section: Discussioncontrasting
confidence: 73%
“…The World Health Organization (WHO) defined the hemoglobin levels of anemia in pregnancy as <11 gr/dl in 2001.12 In our study, the prevalence of anemia in pregnancy has been reported as 25%.12 The estimated prevalence of anaemia in pregnancy differs widely, 58% in China, 50% in South Asia, 40% in Istanbul 13-15. Anemia is seen at different frequencies in different populations.…”
Section: Discussionmentioning
confidence: 83%
“…It affects more than 2 billion people of different age groups worldwide both in developing and developed countries [5,6]. However, it is more prominent in pregnant women (PW), young children and other reproductive age groups [7]. It causes a high morbidity and mortality among antenatal mothers [8].…”
Section: Introductionmentioning
confidence: 99%